1995
DOI: 10.1159/000246633
|View full text |Cite
|
Sign up to set email alerts
|

Oral Calcium Tolerance Test in Extensive Psoriasis Treated with Topical Calcipotriol

Abstract: Background: The vitamin D3 derivative calcipotriol (Daivonex®) is an efficient topical treatment of psoriasis. When applied at a dose of about 25 g/week over a mean body surface of 16%, it is not associated with any detectable change in calcium metabolism. Objective: Our purposes were (i) to analyze the effects of calcipotriol on various parameters of calcium metabolism when applied on a large body surface and (ii) to evaluate the usefulness of an oral calcium tolerance test in monitoring psoriatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In a subsequent study by the same group, 10 patients were treated with up to 95 g calcipotriol ointment (50 µg/g) per week (mean use: 90 g/week) for 6.5 weeks. As in the previous study, no significant changes were demonstrated in a wide variety of parameters of systemic calcium homoeostasis, including an oral calcium test [10]. …”
Section: Introductionmentioning
confidence: 67%
“…In a subsequent study by the same group, 10 patients were treated with up to 95 g calcipotriol ointment (50 µg/g) per week (mean use: 90 g/week) for 6.5 weeks. As in the previous study, no significant changes were demonstrated in a wide variety of parameters of systemic calcium homoeostasis, including an oral calcium test [10]. …”
Section: Introductionmentioning
confidence: 67%
“…[7][8][9]13] [14][15][16][17] • Induces cell differentiation in vitrd8-1o. 13,18,19] and in patients with psoriasis [16.17.20] • Binds to calcitriol receptors [7'9,13] • Modifies levels of immunological and inflammatory mediators: -down-regulates or lowers levels of interleukins (IL-1, IL·6), [21,22] interleukin-8 receptors, [23] T cells (CD3-t, CD4+, CD6+ and CD8+), [16,24,25] cell adhesion molecules (ICAM-1, ELAM-1, LFA-1, VLA-3 and VLA_6) [24.26] and the plasminogen system [27] -up-regulates or increases levels of NGF, [28] TGF_~, [29,30] TGF-~ binding protein [30] and calcitriol receptors [31] • Less potent effect than calcitriol on calcium homeostasis in rats [8,9,32] and humans [33][34][35][36][37][38] Abbreviations: ELAM = endothelial leucocyte molecule; ICAM = intracellular adhesion molecule; LFA = lymphocyte function antigen; NGF = nerve growth factor; TGF = transforming growth factor; VLA = very late antigen.…”
Section: Effects On Cell Proliferation and Differentiationmentioning
confidence: 99%
“…Furthermore, potent hexafluoride analogues can reduce the breast cancer incidence and burden in N-nitroso-N-methylurea-treated rats (39). One area in which the therapeutic potential of vitamin D 3 has been realized is in the treatment of psoriasis, where the topical application of potent analogues, including calcipotriene (Dovonex), controls the disease and does not significantly interfere with serum calcium levels (40).…”
mentioning
confidence: 99%